Routine immunization status of nomadic children aged five years and below in Volta Region, Ghana in the post-COVID-19 pandemic era: a cross-sectional study - Amatus Nambagyira; Samuel Adolf Bosoka; Mavis Pearl Kwabla; Godwin Adjei Vechey; Senanu Kwesi Djokoto; Fortress Yayra Aku (BMC Public Health)
Abstract Background Despite the benefits of routine childhood immunization, coverage has remained low in parts of Ghana, particularly among nomadic children. Moreover, the COVID-19 pandemic exacerbated the uptake of routine immunization and other health services. We, therefore, assessed the routine immunization status of nomadic children aged five years and below during the post-COVID-19 pandemic era in two districts of the Volta Region. Methods Between July and October 2022, we conducted a community-based analytical cross-sectional study among 157 nomadic children aged five years and below to asses post-COVID-19 pandemic immunization status. Data were collected through interviews of caregivers using a structured questionnaire and analyzed with Stata Version 17. Descriptive statistics were used to summarize the data. A multivariate logistic regression model was used to determine factors associated with full immunization status at p < 0.05 and 95% confidence interval. Results Of the 157 children involved in the study, males comprised the dominant group, accounting for 52.2% (82/157). The overall complete immunization for age was 51%, with 73.6% full immunization observed among those aged 12–59 months. The odds of full immunization were higher among children aged 24–35 months [aOR = 15.50, 95%CI: (2.03-118.39)] and those aged 36–59 months [aOR = 14.18, 95% CI: (3.17, 63.46)], children of caregivers with a history of postnatal care (PNC) visits [aOR = 4.16, 95% CI: (1.29–13.40)], caregivers being convenient with the immunization schedule [aOR = 4.50, 95% CI: (1.16–17.42)] and those encouraged by community leaders [aOR = 95%CI: (1.06–13.70)]. Caregivers reporting long waiting times at vaccination centres had lower odds [aOR = 0.19, 95% CI: (0.04–0.84)] of full immunization. Conclusion The full immunization status of nomadic children under five years in the study area was moderate and was associated with the child’s age, PNC visits, community leader encouragement, the convenience of immunization schedules, and waiting times. We recommend that the District Health directorates employ targeted and multifaceted strategies to address the suboptimal immunization uptake observed among this vulnerable group.